Optimizing Preclinical Skill Assessment for Handpiece-Naïve Students: A Strategic Approach - Chau; Reinhard Chun Wang; Felszeghy, Szabolcs; Sittoni-Pino, Maria F.; Arias-Herrera, Santiago; Bencharit, Sompop; Maggio, Margrit; Mutluay, Murat; Rice, David P.; Lam; Walter Yu Hang; Usta, Sila Nur; et al. (MDPI, 2026)
Background: Preclinical dental training requires simulation-based tools to develop fine motor skills, but traditional models like plastic teeth often lack realistic tactile feedback, and systematic evaluations of multi-layered drilling plates are scarce. This study aimed to evaluate the educational utility and perceived realism of a novel multi-layered drilling plate designed to simulate enamel, dentin, and pulp, with null hypotheses that it would not differ in realism from natural dental tissues or in educational utility from existing tools.
Methods: Seventy dental educators (mean preclinical teaching experience: 112.9 +/- 116.7 months) from 14 institutions across four continents assessed the plates using standardized protocols. Statistical analysis (Mann-Whitney U Test) was performed to analyze the results.
Results: Quantitative ratings (1-10 scale) showed high mean scores for drilling quality (enamel: 7.80 +/- 1.55, dentin: 7.27 +/- 1.94, pulp: 7.48 +/- 2.33), surface smoothness (enamel: 8.17 +/- 1.55, dentin: 8.17 +/- 1.57), and ergonomic visibility (8.56 +/- 1.58), with 90% passing grades, rejecting the null hypothesis of no difference in educational utility. Tissue transition scores (enamel/dentin: 7.09 +/- 2.56; dentin/pulp: 6.86 +/- 2.46) showed significant differences (p < 0.05) in realism from natural tissues, rejecting the null hypothesis of no difference. Inter-rater reliability was poor (Krippendorff's alpha: 0.449 for failing scores, 0.211 for passing scores). Qualitative feedback praised ease of use but noted limitations in dentin haptic simulation. Conclusions: The drilling plate shows promise for skill development, though without controlled comparisons to existing tools, its relative efficacy remains preliminary. Further research on student outcomes and tool refinement is needed to validate its use in dental education.